The 2dF QSO Redshift Survey - X. Lensing of Background QSOs by Galaxy Groups - Myers, A; Outram, P; Shanks, T; Boyle, B; Croom, S; Loaring, N; Miller, L; Smith, R (2002)
We cross-correlate QSOs from the 2dF Survey with galaxy groups. The galaxy samples are limited to B < 20.5. We use an objective algorithm to detect galaxy groups. A 3sigma anti-correlation is observed between QSOs and galaxy groups. This paucity of faint QSOs around groups is neither a selection effect nor due to restrictions on the placement of 2dF fibres. By observing the colours of QSOs on the scales of the anti-correlation, we limit dust in galaxy groups, finding a maximum reddening of E(b_j-r) < 0.012 at the 95% level. The small amount of dust thus inferred is insufficient to cause the anti-correlation, supporting the suggestion by Croom and Shanks that the signal is due to gravitational lensing. The possibility remains that tailored dust models, such as grey dust, heavy patches of dust or a combination of dust and lensing, could explain the anti-correlation. Assuming the signal is caused by lensing rather than dust, we measure the average velocity dispersion of a Singular Isothermal Sphere that would cause the anti-correlation as around 1150 km/s. Simulations reject 600 km/s at the 5% significance level. We also model foreground lenses as NFW haloes and measure the typical mass within 1.5 Mpc/h of the halo centre as M_{1.5} = (1.2 +/- 0.9) x 10^{15} solarmasses/h. Regardless of whether we utilise a SIS or NFW dark matter profile, our model favours more mass in groups than accounted for in a universe with density parameter Omega_m = 0.3. Detailed simulations and galaxy group redshifts will significantly reduce the current systematic uncertainties in these $Ω_m$ estimates. Reducing the remaining uncertainty will require larger QSO and galaxy group surveys (abridged).